Job Reallocation and Productivity Growth under Alternative Economic Systems and Policies: Evidence from the Soviet Transition - J. David Brown; John S. Earle (W.E. Upjohn Institute for Employment Research, 2002)
How do economic policies and institutions affect job reallocation processes and their consequences for productivity growth? This paper studies the extreme case of economic system change and alternative transitional policies in the former Soviet Republics of Russia and Ukraine. Exploiting annual industrial census data from 1985 to 2000, we find that Soviet Russia displayed job flow behavior quite different from market economies, with very low rates of job reallocation that bore little relationship to relative productivity across firms and sectors. Since liberalization began, the pace, heterogeneity, and productivity effects of job flows have increased substantially. The increases occurred more quickly in rapidly reforming Russia than in "gradualist" Ukraine, as did the estimated effects of privatization and competitive pressures from product and labor markets on excess job reallocation and on the productivity-enhancing effects of job flows.
Keywords: E24; J63; O47; P23; 330; Russia; Ukraine; economy; work; transition; productivity; Earle; Brown